PENERAPAN GOOGLE EART SEBAGAI ALAT MONITORING KASUS TUBERCULOSIS DI PUSKESMAS DELI TUA TAHUN 2021 - Firdaus Fahdi; Bahtera Bindavid Purba; Herviani Sari (INSTITUT KESEHATAN DELI HUSADA, 2022)
The Community Partnership Program is one of the research programs that was carried out in 2021 in the Deli Tua Health Center work area. This program was conducted to validate the prototype of the tuberculosis monitoring system. In 2020 the number of new tuberculosis (TB) cases (notified TB) in the working area of the Deli Tua Health Center reached 143 cases with a success rate of 76% and MDR TB reaching 15%. This decrease in cases was caused by: 1) taking medication on time and the wrong dose of MDR TB treatment and 2) non-adherence to taking medication. To solve the problem, google earth mapping and calendar documentation have been applied. The results of the implementation showed that there was a significant difference in the completeness of treatment before and after the intervention (RR=2.21; 95%CI: 1.32-3.69), the cure rate for tuberculosis cases (RR=1.87; 95%CI: 1 .17-2.99), treatment drop-out rate (RR=1.77; 95%CI: 1.07-2.95), and mortality rate (p<0.01).